Innovation Models and Business Concepts as Context for Radical Innovation in Freshwater Fish Trading Applications. - Sandy, Muhammad Dwi Hary; Abdurrahman, Lukman; Fakhrurroja , Hanif (eProceedings of Engineering, 2025)
Indonesia is a maritime country with abundant fishsheries resources potential. However, fishsh farmers often face challenges in terms of profisht margins and marketing of their catches. An alternative is needed for fishsh sales activities that are anti-price wars and customeroriented. this is due to the lack of market information, so farmers think it is more e昀케cient to sell their harvest to middlemen or collectors because they don’t need to fishnd customers in the market and incur transportation costs for fishsh delivery. However, because of this, the price of fishsh sold will become more expensive with each transfer to a third party, and the profisht margin for fishsh farmers remains small. Based on these problems, the author aims to provide a solution for fishsh farmers by designing an application for fishsh trading transactions. this research utilizes a Design thinking approach simplifished into the stages of the RSM (Recognize, Scrutinize, Materialize) Design Approach in application development. this model is aligned with addressing issues such as low profisht margins and the challenges of independent sales. It also emphasizes the need for collaboration in sales management, such as the existence of digital fishsh cooperatives. Keywords : eFishery Fresh, Radical innovation, RSM model